The "Doomsday" effect in climate policies: Why is the present decade so crucial to tackling the climate challenge? - Baptiste Perrissin Fabert; Etienne Espagne; Antonin Pottier; Patrice Dumas (Fondazione Eni Enrico Mattei (FEEM), 2012)
Despite growing scientific evidence that passing a 2êC temperature increase may trigger tipping points in climate dynamics, most Integrated Assessment Models (IAM) based on Cost Benefit Analysis (CBA) with smooth quadratic damage functions are unable to account for the possibility of strong increase in climate damage. Our IAM RESPONSE makes it possible to bridge this gap by integrating a threshold effect damage function which sets a threshold of temperature increase from which climate damages increase significantly. To fit with on-going climate negotiations, this threshold is set at 2êC. Regardless of the bleak prospect of passing the threshold, it turns out that among a broad set of scenarios accounting for the diversity of worldviews in the climate debate, overshooting the 2êC target and then facing the resulting damage may become an optimal strategy for many economic agents who are struck by what we call a doomsday effect. We show that this effect happens for any level of jump in damage and dramatically increases if the beginning of mitigation efforts is postponed till the decade 2010-2020 on. In light of these results, we believe that any further delay in reaching a clear international agreement will close the window of opportunity for meeting the 2êC target with a reasonable chance of diplomatic success.
Keywords: C61; Q54; Q58; 330; Integrated Assessment Model; Non Linear Effect; Doomsday Effect; 2êC Target